2012
DOI: 10.1111/j.1600-6143.2011.03888.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Pediatric Access to Kidney Transplantation: Does Socioeconomic Status Play a Role?

Abstract: Racial disparities persist in access to renal transplantation in the United States, but the degree to which patient and neighborhood socioeconomic status (SES) impacts racial disparities in deceased donor renal transplantation access has not been examined in the pediatric and adolescent end-stage renal disease (ESRD) population. We examined the interplay of race and SES in a population-based cohort of all incident pediatric ESRD patients <21 years from the United States Renal Data System from 2000 to 2008, fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
107
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 44 publications
(64 reference statements)
4
107
0
1
Order By: Relevance
“…2 Historically, black pediatric ESRD patients have reduced access to the waiting list, wait longer to receive a transplant, and are more likely to experience graft failure compared with white pediatric ESRD patients. [3][4][5][6][7][8] The racial differences observed in pediatric kidney transplantation are multifactorial and likely influenced by a complex mixture of biologic, immunologic, and socioeconomic factors. Some of the factors that have been thought to play a role include decreased rates of living-donor (LD) kidneys and pre-emptive transplantation, greater histocompatibility mismatches, and lower socioeconomic status (SES) among black versus white pediatric ESRD patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2 Historically, black pediatric ESRD patients have reduced access to the waiting list, wait longer to receive a transplant, and are more likely to experience graft failure compared with white pediatric ESRD patients. [3][4][5][6][7][8] The racial differences observed in pediatric kidney transplantation are multifactorial and likely influenced by a complex mixture of biologic, immunologic, and socioeconomic factors. Some of the factors that have been thought to play a role include decreased rates of living-donor (LD) kidneys and pre-emptive transplantation, greater histocompatibility mismatches, and lower socioeconomic status (SES) among black versus white pediatric ESRD patients.…”
mentioning
confidence: 99%
“…Some of the factors that have been thought to play a role include decreased rates of living-donor (LD) kidneys and pre-emptive transplantation, greater histocompatibility mismatches, and lower socioeconomic status (SES) among black versus white pediatric ESRD patients. 3,[8][9][10][11] Little information has been reported on transplant access in Hispanic children with ESRD; however, the work by Leonard et al 4 found a reduced rate of transplantation among Hispanic versus white pediatric incident dialysis patients. The work by Patzer et al 8 recently reported reduced access to deceased-donor kidney transplantation (DDKT) for both black and Hispanic pediatric incident ESRD patients compared with whites, even after adjusting for individual and neighborhoodlevel measures of SES.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnic minorities, women, older adults, patients with lower socioeconomic status, and those on dialysis at a for-profit center are less likely to undergo kidney transplantation. Among pediatric patients, ethnic minorities tend to have reduced access to the transplant waiting list, have reduced access to deceased donor transplantation once on the waiting list [32], and to livingdonor preemptive transplantation [33]. Although ethnicity and social deprivation are closely related, socioeconomic status does not explain all ethnic differences in access to pediatric kidney transplantation in the US [32].…”
Section: Inequalities In Access To Transplantationmentioning
confidence: 99%
“…Among pediatric patients, ethnic minorities tend to have reduced access to the transplant waiting list, have reduced access to deceased donor transplantation once on the waiting list [32], and to livingdonor preemptive transplantation [33]. Although ethnicity and social deprivation are closely related, socioeconomic status does not explain all ethnic differences in access to pediatric kidney transplantation in the US [32]. A change in the national allocation policy in 2005, which gave a higher priority to pediatric candidates, has attenuated, but not eliminated, these ethnic disparities [34].…”
Section: Inequalities In Access To Transplantationmentioning
confidence: 99%